Reviewing the Medical Record Confidentiality of Covid-19 Patient - Hezron Sabar Rotua Tinambunan; Elisabeth Septin Puspoayu; Eliza Tiurmaida (Jurnal Dinamika Hukum, 2021)
The Government has done several efforts in order to handling the Covid-19 virus, such as through an appeal to maintain personal hygiene, keep a safe distance, and do not come in direct contact with others. The spread of this appeal was carried out on various platforms, ranging from advertisements on television nor social media. The coverage through the media includes which areas have been exposed by Covid-19, the number of people who have been considered infected, recovered, and the number of people who have died from the virus. Oftentimes, the news is followed by the dissemination of the peoples identity, on the grounds that the public should be more careful, whereas the patient’s identity is strictly protected based on the patient’s right to privacy or medical confidentiality. This writing uses a normative juridical research method. The issues raised were related to the privacy rights and medical confidentiality in the handling of Covid-19. Article 51 of Law No. 29/2004 concerning Medical Practice stated that a doctor is obliged to keep all the information about the patient, even after the patient died. This uphold the fact that a medical confidentiality are closely related to human rights.Keywords: Covid-19; Medical confidentiality; Patient